2016
DOI: 10.1021/acs.nanolett.6b03268
|View full text |Cite
|
Sign up to set email alerts
|

Structural Attributes and Photodynamics of Visible Spectrum Quantum Emitters in Hexagonal Boron Nitride

Abstract: Newly discovered van der Waals materials like MoS, WSe, hexagonal boron nitride (h-BN), and recently CN have sparked intensive research to unveil the quantum behavior associated with their 2D structure. Of great interest are 2D materials that host single quantum emitters. h-BN, with a band gap of 5.95 eV, has been shown to host single quantum emitters which are stable at room temperature in the UV and visible spectral range. In this paper we investigate correlations between h-BN structural features and emitter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
268
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(299 citation statements)
references
References 66 publications
17
268
3
5
Order By: Relevance
“…Some color centers, such as the nitrogen vacancy (NV) center in diamond [6][7][8][9][10][11], are bright enough to be investigated in the single defect limit using single-molecule microscopy techniques [12,13]. While diamond is the most celebrated host material, the last several years have witnessed the discovery of defect-based single photon sources in SiC [1,[14][15][16][17][18][19][20], ZnO [21][22][23][24][25][26], GaN [27], WSe2 [28][29][30], WS2 [31], and hexagonal boron nitride (h-BN) [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The latter three materials exist as two-dimensional monolayers and layered solids, thus offering the possibility of integrating single-photon sources with van der Waals heterostructure devices for tuning and other control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some color centers, such as the nitrogen vacancy (NV) center in diamond [6][7][8][9][10][11], are bright enough to be investigated in the single defect limit using single-molecule microscopy techniques [12,13]. While diamond is the most celebrated host material, the last several years have witnessed the discovery of defect-based single photon sources in SiC [1,[14][15][16][17][18][19][20], ZnO [21][22][23][24][25][26], GaN [27], WSe2 [28][29][30], WS2 [31], and hexagonal boron nitride (h-BN) [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The latter three materials exist as two-dimensional monolayers and layered solids, thus offering the possibility of integrating single-photon sources with van der Waals heterostructure devices for tuning and other control.…”
mentioning
confidence: 99%
“…Defect emission in h-BN can be ultrabright [32], have a narrow linewidth [33], be tuned [39], and remain photostable up to 800 K [41]. These positive attributes have sparked strong interest in h-BN defects from research groups around the world [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Despite this surge of interest, most works have focused on characterizing the phenomenology of h-BN emission, leaving open several difficult to answer questions regarding the fundamental nature of h-BN quantum emitters.…”
mentioning
confidence: 99%
“…HBN is already an ubiquitous dielectric in van der Waals heterostructures [12], and it is emerging as a versatile platform for nanophotonics [13]. Recent experiments have identified point-like quantum emission at visible to near-infrared wavelengths from hBN [14][15][16][17][18][19]. These emitters appear to be robust to the preparation * Present address: Department of Physics, Lafayette College, Easton, PA 18042, USA.…”
mentioning
confidence: 99%
“…However, it has been recently reported that crystal structure imperfections or disorder in some 2D materials such as WSe 2 [10][11][12][13][14] and h-BN [15][16][17] can act as efficient carrier trapping centers that behave as SPEs. In this section, we use the modified MST for the study of the conditions that maximize the extraction of quantum light in 2D WSe 2 and h-BN deposited on SiO 2 /Si and Al 2 O 3 /Al substrates.…”
Section: Optimizing Single-photon Extraction In 2d Wse 2 and H-bnmentioning
confidence: 99%
“…However, potential applications of 2D materials are not only limited to these technologically relevant fields. Very recently, some 2D materials such as WSe 2 [10][11][12][13][14] and h-BN [15][16][17] have revealed promising capabilities for the development of new quantum light sources. Crystal structure imperfections or disorder found in these materials can act as efficient carrier trapping centers that behave as sources of single-photon emitters (SPEs).…”
Section: Introductionmentioning
confidence: 99%